Research Progress of Anti-breast Cancer Peptides - Sun, Zhi-Gang; Li, Zhi-Na; Zhao, Liang-Hui; Zhang, Jin-Mai (International Journal of Innovative Research in Medical Science, 2019)
Breast cancer is a malignant tumor that occurs in the epithelial tissue of the breast, mostly in female. At present, drug resistance has emerged in the treatment of breast cancer. Therefore, the discovery of new drugs for breast cancer is particularly important. Some peptides have been found to have anti-cancer effects. This article reviews the recent discoveries of anti-breast cancer peptides, hoping to provide some help for the development of breast cancer treatment.